EFEKTIVITAS MEDIA PEMBELAJARAN GAME MEGASUS BERBASIS ANDROID TERHADAP PEMAHAMAN MATERI PERSAMAAN GARIS LURUS SISWA KELAS VIII SMPIT ALAM PERMATA PROBOLINGGO - Bachtiar Aziz Affandy; Tuhfatul Janan (LPPM Institut Ahmad Dahlan Probolinggo, 2024)
Learning media is designed to improve the efficiency of teaching and learning activities. The performance of learning media that has been developed needs further research with the aim of knowing the level of effectiveness. This study emphasized to determine the effectiveness of using megasus game learning media based on android with a focus on straight line equation material. This research was conducted in August 2023 in the odd semester of the beginning of the school year to class VIII students of SMPIT Alam Permata Probolinggo, with straight line equation material that had not been taught to the class. In the research flow, a data normality test was carried out using the shapiro-wilk method, where the pre-test significance results showed a figure of 0.286 and a post-test figure of 0.524 so that it could be concluded that the data was normally distributed. Then continued the normality gain test to determine the effectiveness of this android-based megasus game learning media with an average N-gain score of 0.4665 and an average N-gain percent of 46.6532%. Keywords: learning media, straight line equation, mathematics